Environmental institutionality and conflicts of interest: the case of the Dominga mining project in Chile - Gaete Quezada, Ricardo (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The objective of the article is to analyse the functioning of the environmental institutionalism in Chile from the perspective of the main news frames of the Chilean digitalnewspapers during the last five years, related to the environmental impact assessment procedure of the Minera Dominga project. Through a qualitative content analysis, 263 news items published by three national newspapers are examined, allowing the identification of three major informative frameworks of the news about the case study: 1) environmental institutions, 2) impacts, and 3) corruption. These news frames expose the various political, social andjudicial complexities that have been related to the environmental evaluation procedure in force in Chile for more than a decade. One of the conclusions of the study emphasizes the important social responsibility that the media have regarding the dissemination of informationon the environment and the more sustainable development of the territories, which is reflected in the case studied in the publication of different journalistic reports. to denounce actions committed by political and business actors related to irregular situations from a legal point of view that have affected the credibility of citizens, thus increasing the relevance for public opinion of those information frames that are most critical of extractives policies that do notcontribute effectively to the care of the country’s natural resources.